The Role of Jamia Rizvia Faisalabad in Contribution of Islamic Teachings: جامعہ رضویہ فیصل آباد کا دینی علوم کی تدریس اور اشاعت میں کردار - Muhammad, Faqir; Ahmed, Professor Dr. Matloob; Shahzad, Dr. Jameel Ahmad (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
JamiaRizvia “Mezher-ul-Islam” is located in Jhang Bazar Faisalabad. This great Islamic Institute was founded by HazratAllamaSardar Ahmad Chishti Qadri who was great Islamic Scholar, Researcher and Learned personality in the discipline of Quran, Hadith, Islamic Jurisprudence and Arabic Language.TheJamiaRizvia has produced many Ulamas, Orators, Debaters and Authorswhich are serving as Islamic Preachers, CivilGovernmental servants in different official Institution. This Islamic Institute is not only delivering the Islamic and Arabic studies but also current educational courses like as: English, Urdu, Mathematics, Sociology, and Computer Science Pak Studies. So, it can be said that the scholar qualified from this Institution has full command over the Islamic and Modern knowledges. Dueto great effective and appreciable way of Teaching, the last degree of Dars-i- Nizami(Al.Shahadat-ul-Alimyya)is considered equivalent to M.A Islamiat and Arabic.